The mission of development : religion and techno-politics in Asia - Scheer, Catherine. (Theology and Mission in World Christianity, 2018)
The Mission of Development interrogates the complex relationships between Christian mission and international development in Asia from the 19th century to the new millennium. Through historically and ethnographically grounded case studies, contributors examine how missionaries have adapted to and shaped the age of development and processes of 'technocratisation', as well as how mission and development have sometimes come to be cast in opposition. The volume takes up an increasingly prominent strand in contemporary research that reverses the prior occlusion of the entanglements between religion and development. It breaks new ground through its analysis of the techno-politics of both development and mission, and by focusing on the importance of engagements and encounters in the field in Asia.